Care for your Goldfish. - Hearne, Tina.; Royal Society for the Prevention of Cruelty to Animals (Collins, 1990)
In the 150th anniversary year of the royal patronage of the Royal Society for the Prevention of Cruelty to Animals, the publishers are re-launching a revised and enlarged edition of 10 of the titles in this family-oriented pet care series.
Keywords: Goldfish